Ancaman Kepunahan dan Strategi Pemertahanan Tradisi Sinrili di Masyarakat Makassar - Fitriani, Fitriani; Fitriana, Fitriana; Nasir, Nur Hafsa (Paradigma: Jurnal Kajian Budaya, 2022)
This study aims to determine the factors causing the threat of extinction and the strategy of maintaining the sinrili tradition in the Makassar community. This study is based on library research with a descriptive approach. The results of this research reveal that the factors that cause the threat of extinction of the sinrili tradition in the Makassar community are:(1) Work as a singer is not considered as a main profession in Makassar, and is only seen as a side job. (2) The development of modern music which is more attractive to the younger generation poses a challenge to this tradition. (3) The quantity of sinrili in Makassar has deteriorated because the three sinrili maestros have died. There are five strategies for maintaining the sinrili tradition in the Makassar community, namely (1) the provision of a forum by the Government, in this case, the Office of Culture to form a sinrili community (2) developing the interest of the younger generations by holding cultural festivals and having sinrili competitions (3) teaching the sinrili tradition through art circles or clubs (4) documenting the sinrili oral literature, and (5) including the sinrili tradition in the teaching materials of local content subjects of Makassar regional culture. From the results of this research, it can be concluded that currently the process of regenerating singers is still going on through the process of legacy and learning, but at present, there is only one person who is good at singing and performing sinrili, namely Arif Rahman Daeng Rate. Thus, the condition of the sinrili tradition requires serious attention from all parties so that this tradition will remain sustainable and not go into extinction.